Perioperative Considerations in Liver Transplantation - Barjaktarevic, Igor; Cortes Lopez, Roxana; Steadman, Randolph; Wray, Christopher; Qadir, Nida; Chang, Steven Y.; Wang, Tisha (Seminars in Respiratory and Critical Care Medicine, 2018)
Liver transplantation (LT) has the potential to cure patients with acute and chronic liver failure as well as a number of hepatic and biliary malignancies. Over time, due to the increasing demand for organs as well as improvements in the survival of LT recipients, patients awaiting LT have become sicker, and often undergo the procedure while critically ill. This trend has made the process of preoperative assessment and planning, intraoperative management, and postoperative management even more crucial to the success of LT programs. Multidisciplinary and specialized teams are essential and include anesthesiologists, surgeons, and intensivists. This article focuses on the preoperative evaluation, intraoperative care, and postoperative management of the liver transplant patient. Management relevant to the critically ill patient is discussed, with a focus on the management of postoperative cardiopulmonary conditions including the care of special populations such as those with hepatopulmonary syndrome and portopulmonary hypertension.
Keywords: liver transplantation; anesthesia; end-stage liver disease; postoperative critical care; hepatopulmonary syndrome; portopulmonary hypertension